Effectiveness of Basic AI Learning Using Teachable Machine on Understanding Classification Concepts among Vocational High School Students: Experimental Study - Lisnayu; Tirstan Anugerah Ranus; Muh Yusril Mahendra; M. Rifqi Miftahun Nurulhad; Zulkarnain; Dita Adelina (Jurusan Teknik Informatika dan Komputer, 2024)
The purpose of this study is to explore the effectiveness of Teachable Machine, an AI-based tool, in enhancing vocational high school students' understanding of classification concepts in machine learning. Given the increasing importance of AI in education, particularly in vocational settings, this study aims to investigate how interactive learning tools can foster deeper conceptual understanding and improve engagement in technical fields. This experimental study involved two groups of vocational high school students: an experimental group using Teachable Machine and a control group receiving traditional classroom instruction. The students' understanding of classification concepts was measured using pre-tests and post-tests, supplemented by qualitative observations of student engagement. Statistical analyses, including paired t-tests and Cohen’s d for effect size, were conducted to assess the difference in learning outcomes between the groups. The experimental group showed significant improvement in post-test scores compared to the control group. The paired t-test results indicated a larger effect size (Cohen’s d = 1.55) for the experimental group, demonstrating a substantial improvement in their understanding of classification concepts. Qualitative observations also revealed higher levels of student engagement and motivation in the experimental group. The study highlights the potential of AI-based tools to improve learning outcomes in vocational education. However, limitations include the small sample size and the short duration of the intervention, which may limit the generalizability of the findings. Future research should explore the long-term effects and compare different AI tools. This study provides valuable evidence of the effectiveness of AI-based learning tools in vocational education, contributing to the growing body of research on AI applications in education. It also offers insights for integrating interactive learning tools into vocational curricula to enhance student engagement and understanding.